2019
DOI: 10.4102/jamba.v11i1.638
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the plan: How land use control practices influence flood risk in Sekondi-Takoradi

Abstract: Using a pragmatic philosophical underpinning, this article analyses how land use planning actions and inactions contribute to flood risk creation in Sekondi-Takoradi, Ghana. In recent times, the planning system in Ghana has come under intense public criticism for failure to effectively control physical development in the major cities. The recurring flooding in the cities of Accra, Kumasi, Tamale and Sekondi-Takoradi seems to testify to this failure. Many lives and property have been lost through these flooding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Finding from Amoako and Inkoom [21] also revealed that rainfall intensity or storm surges trigger flash flood in urban areas. Research demonstrated that urban flood in Ghana occur due to poor drainage system [27], poor waste management [28], removal of urban vegetation [23] and poor urban and structural planning [23,29]; however, the planning system in Ghana has failed to successfully control urban physical development [30] and this has exacerbated the effects of urban flooding.…”
Section: Gap Analysis and Goals Of Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding from Amoako and Inkoom [21] also revealed that rainfall intensity or storm surges trigger flash flood in urban areas. Research demonstrated that urban flood in Ghana occur due to poor drainage system [27], poor waste management [28], removal of urban vegetation [23] and poor urban and structural planning [23,29]; however, the planning system in Ghana has failed to successfully control urban physical development [30] and this has exacerbated the effects of urban flooding.…”
Section: Gap Analysis and Goals Of Reviewmentioning
confidence: 99%
“…A total of 18 articles were identified and coded for patterns in data [65]. Eighteen studies reported poor urban planning and development as the causes of flood, for instance, [23,29,57,66]. Next, 11 studies reported on poor drainage network, for instance, [27,67,68].…”
Section: Delimitation and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second lesson from the case of Guangzhou is that the success of coordination across levels of government relies on the presence of a set of clear and specific tools and indicators for translating national policy goals into local plans and policies. Both of these lessons are helpful in responding to the flood governance challenges observed in other cities across the world [8][9][10]. The potential challenges concerning the capacity of planners to tackle flood issues and governance conflicts, such as those mismatches concerning administrative and water basin boundaries portrayed in this paper, require great attention.…”
Section: Discussionmentioning
confidence: 89%
“…This concern emerges in recent planning literature and stresses how statutory regulations can affect the progress of implementation and the enforcement of legal obligations when they are imposed upon planners, developers, and individuals. For example, in the United Kingdom, authorities increasingly require planners to restrict constructions in flood-prone areas to reduce flood exposure [9]; or, in Ghana, the poor enforcement of planning permission makes it impossible to restrict illegal urban construction which increases vulnerability to flood [10]. A similar concern arises more often in climate mitigation and adaptation studies: strong legal mandates of the authorities or the mandatory character of agreements may, in some cases, facilitate the effectiveness of agents' actions by providing resources or knowledge and shaping the perceptions of the issue [11,12].…”
Section: Introductionmentioning
confidence: 99%